Theoretical fundamentals of Neoliberalism: some notes from Foucault, Dardot and Laval - Correia, Fabio Caires [UNESP]; Duarte, Fabio Henrique; Perius, Oneide (Univ Federal Piaui, Editora, 2023)
The anti-democratic turn produced by neoliberalism is, without a doubt, a sign of our times. But here we intend to show that studying it as a logical consequence of a new political rationality results in the painting of a total apocalyptic picture (1) for democracy, (2) for politics and (3) for the subject. If we could continue to think of neoliberalism as an ideology, whose field of forces would work with very well-defined mechanisms, but not as a radical transformation of the modes of political domination, it would be possible to understand the de-democratization that characterizes our time in the context in which which is currently understood as thinkers inscribed in the Marxist tradition, i.e., as a new chapter in the historical tension between capitalism and democracy. In the present paper, we intend to reconstruct the notion of rationality, in Foucault, as it began to appear In Defense of Society and the way in which this notion is definitively associated with neoliberalism in The birth of biopolitics, with a view to specifying the way in which its novelty is articulated there. In a second moment, we present the conflict between this new form of government and democratic politics, suggested by the texts of Dardot and Laval. Last but not least, we point out the epistemological limits that the Foucauldian perspective has to study the democratization processes that permeate contemporary capitalist societies from the concept of neoliberal rationality.
Keywords: Neoliberalism; Subjectivation; Biopolitics; World reason